Water quality characteristics in the waters of Pangempang, Muara Badak, East Kalimantan - Wisnuardi, Doa; Eryati, Ristiana; Suryana, Irma (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
The Pangempang waters, located within the estuarine area of Muara Badak, have experienced continuous coastline changes due to annual erosion. Monitoring water conditions in this region is essential to evaluate environmental suitability and detect potential threats. This study examined the physical and chemical properties of the water, following the guidelines of Government Regulation No. 22 of 2021. Observations were conducted at five selected sites: a shrimp pond, a river area adjacent to the pond, the river mouth near mining activities, a tourist area on Pangempang Island, and the outer section of the island near the dock, representing the Pangempang waters. Overall, the results indicate that water quality remains within acceptable limits for marine biota. However, certain parameters, such as temperature, salinity, and nitrate levels, deviated from the established standards. These variations are influenced by weather conditions, location, and potential organic waste input from activities along the study area.